Genome-wide molecular characterisation of central nervous system primitive neuroectodermal tumours and pineoblastomas - Miller, Suzanne (2010)
CNS PNET and pineoblastomas are highly malignant embryonal brain tumours of poor prognosis. Current treatment strategies are based on the histologically similar medulloblastoma; however, patients with CNS PNET and pineoblastoma have significantly worse outcomes. Specific therapies based on the underlying biology and genetics of CNS PNET and pineoblastoma are needed. To provide evidence of the fundamental genetics driving tumour pathogenesis and to identify novel targets for therapy, 46 CNS PNETs and pineoblastomas were analysed using the Affymetrix 100K/500K mapping sets to identify genome-wide copy number alterations and loss of heterozygosity. Overall, frequent gains of 1q, 2p and 21q and frequent loss of 16q were identified. Unsupervised hierarchical clustering showed marked differences in the frequency of genetic imbalance in the CNS PNETs and pineoblastomas, with pineoblastomas containing fewer genomic changes clustering separately to the CNS PNETs. Novel gene copy number alterations were identified; gain of PCDHGA3 (5q31.3) and FAM129A (1q25) and losses of OR4C12 (11p11.12), CADPS (3p14.2), and SALL1 (16q12.1). Loss of CDKN2A and CDKN2B was also identified, in keeping with previous genetic studies of CNS PNET. Linking gene copy number data with patient clinical information, loss of CADPS was associated with poor prognosis in patients with primary CNS PNETs (p = 0.033 and p = 0.046, by SNP array and real time qPCR analyses, respectively). On comparison of 5 primary and recurrent CNS PNET pairs, gain of 2p21 was the most common alteration maintained in 80% of cases. Immunohistochemistry for p15INK4B (encoded by CDKN2B) was performed which demonstrated the loss in gene copy number had lowered the expression of the encoded protein. Finally an immunohistochemical and mutational screen for INI1 (commonly lost in the malignant embryonal brain tumour, ATRT) was performed in the CNS PNET/pineoblastoma cohort which showed the loss of INI1 protein expression in the tumour cohort was not due to mutations residing in the mutational hotspots of exons 5 and 9 of the INI1 gene. Patients with INI1 immunonegative CNS PNETs had a worse prognosis than those with INI1 immunopositive CNS PNETs (p < 0.0001). This project demonstrated the first application of SNP array technology in the analysis of the largest cohort of CNS PNETs and pineoblastomas to date, identified novel gene copy number alterations, linked genetic alterations with clinical factors and identified 2 potential markers of prognosis.